(untitled) (Delta Medical College Journal, 2020)
Background: Gastric ulcer is one of the common diseases worldwide. Different parts of Azadirachta indica (Neem) tree has different uses in medicine for its beneficial properties and its leaves are also known to have anti ulcerant effect. Objective: This study was conducted to find out the protective role of Azadirachta indica (Neem) extract in the development of gastric ulcer. Materials and method: The study comprised of 30 Albino rats: Group-A, Group-B, Group-C, Group-D and Group-E having 6 rats in each group. The experiment was divided into 2 parts: Experiment-1 and Experiment-2. Experiment-1 comprised of Group-A and Group-B where Group-A served as control and was provided with normal saline (2 ml/kg body wt). In group-B rats ulcer was produced by administration of aqueous suspension of Aspirin (200 mg/kg body wt). All the rats were sacrificed after 4 hours to confirm gastric ulcer by histopathology. In Experiment-2, rats of Group-C served as disease control group and provided with normal saline (2ml/kg body wt). Group-D was provided with alcoholic extract of Azadirachtaindica leaves (150mg/kg body wt) and Group-E was provided with Ranitidine suspension (20mg/kg). After 8 days of treatment, animals were fasted for 24 hours. Then aqueous suspension of Aspirin (200 mg/kg body wt) was administered and after 4 hours all rats were sacrificed. Gross and microscopic examinations were performed to evaluate the results. Results: Histologically Aspirin treated rats showed ulcerated mucosa. Pretreatment with Neem extract showed protection against Aspirin induced gastric mucosal damage which was statistically highly significant (p<0.001). Conclusion: The study suggests that pretreatment with Azadirachta indica (Neem) leaves extract may be useful in prevention of Aspirin induced gastric ulcer. Delta Med Col J. Jul 2019 7(2): 61-65